Bioactivity of Medicinal Plants Piper nigurm and Tamarindus indica against Heterotermes indicola (Wasmann) - Rafia Tabassum; Ayesha Aihetasham (BioScientific Review, 2024)
Background. Termites, notorious for causing significant damage to crops, plantation forests, and buildings, pose a serious threat as pests. Conventional control methods rely on the use of insecticides, which have been reported to be hazardous to various other forms of life as well. In contrast, lower termites host protozoa in their gut, facilitating cellulose digestion through the release of cellulase enzymes.Method. This study explored the efficacy of ethanolic leaf extracts from two medicinal plants namely Piper nigrum and Tamarindus indica against Heterotermes indicola (Wasmann). GC-MS analysis of the plant extracts revealed their distinct chemical compositions.Results. The T. indica extract comprised compounds such as Benzene, 1,1’(1-methylethylidene) Bis [4-methoxy, 3-0-Methyl-d-glucose, Benzoic acid, 3,4,5-trihydroxy-, methyl ester, 9,12,15, octadecatyrien-1-ol, (Z, Z, Z), 1,3,3-Trimethyl-2-hydroxymethyl3,3-dimethyl-4-(3-methylbut-2-enyl), Di-n-decylsulfone, and 2R-Acetoxymethyl-1,3,5-trimethyl4c-(3-methyl-2-buten-1-yl)-1ccyclohexanol. On the other hand, P. nigrum extract contained Octacosanol, Urs-12-en-24-oic acid, 3-oxo-, methyl ester, (+)-, B-Amyrin, Behenic alcohol, and Humulane-1,6-dien-3-ol. Both plant extracts exhibited repellent properties against H. indicola.Conclusion. The LC50 values for T. indica and P. nigrum were found to be 14.83% and 12.20%, respectively. While, the LC90 values for T. indica and P. nigrum were -4.26% and -1.19%, respectively.